2022
DOI: 10.3390/agronomy12081788
|View full text |Cite
|
Sign up to set email alerts
|

Algal-Mediated Nanoparticles, Phycochar, and Biofertilizers for Mitigating Abiotic Stresses in Plants: A Review

Abstract: The excessive use of agrochemicals to ensure food security under the conditions of a growing population, global climate change, weather extremes, droughts, wasteful use of freshwater resources, and land degradation has created severe challenges for sustainable crop production. Since the frequent and abrupt environmental changes are outcompeting the existing agricultural technologies of crop production systems to meet food security, the development and use of modern technologies and nature-based solutions are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 202 publications
(168 reference statements)
1
5
0
1
Order By: Relevance
“…A plethora of studies have confirmed our current findings where MDA, H 2 O 2 , O 2 − , and OH − increased with an increase in drought severity [7][8][9]17,19,28,70]. In contrast, BC application substantially reduced ROS-mediated stress in L. fusca, which was also confirmed by the earlier studies [15,32,35,68,[81][82][83]. As well as ROS, recent studies revealed that, as a result of excessive lipid peroxidation, some reactive carbonyl species (RCS) are also produced, which cause oxidative injury to plant cells [11,84].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A plethora of studies have confirmed our current findings where MDA, H 2 O 2 , O 2 − , and OH − increased with an increase in drought severity [7][8][9]17,19,28,70]. In contrast, BC application substantially reduced ROS-mediated stress in L. fusca, which was also confirmed by the earlier studies [15,32,35,68,[81][82][83]. As well as ROS, recent studies revealed that, as a result of excessive lipid peroxidation, some reactive carbonyl species (RCS) are also produced, which cause oxidative injury to plant cells [11,84].…”
Section: Discussionsupporting
confidence: 91%
“…BC-2 also exhibited similar stimulation in the activities of antioxidants for both drought levels. Additionally in shoots, the amino acid content including Ala, Gly, Leu, Pro, Val, Trp, Tyr, Lys, Ser, Thr, Cys, Met, Asn, Gln, His, Arg, Glu, and Asp declined by 37,42,31,17,31,43,41,40,18,30,24,27,27,35,28,53,39, and 43% by 70% FC, and this reduction was 64,77,71,76,81,84,72,73,79,62,53,78,76,86,53,77,82, and 70% after the employment of 30% FC, respectively (Figure 6). Similar to the up-regulation of amino acids in roots, The shoots of L. fusca plants experienced 17, 25, 17, 39, 29, 26, 32, 55, 32, and 19% inhibition in organic acid content after 70% FC, and a 58, 75, 65, 68, 58, 71, 63, 85, 67, and 67% decline in CA, FA, LA, SA, BA, MA, PA, OA, GA I, and GA II following 30% FC, respectively.…”
Section: Biochar-dependent Changes In Antioxidant Activities Under Dr...mentioning
confidence: 98%
“…Algae are readily available and eco-friendly, with rich source of metabolites and optimum metal uptake capacity for use as reducing agents for nanoparticle synthesis ( Abideen et al., 2022 ; Hasnain et al., 2022 ). In addition, algae accumulate higher lipids and potential source of biodiesel using saline lands and brackish water.…”
Section: Synthesis Of Engineered Nanomaterialsmentioning
confidence: 99%
“…One of the most recent technologies that has attracted interest across several fields is nanoparticles (NPs). It is thought that the biological synthesis of NPs (using, for example, microorganisms such as bacteria, fungi and yeast, microalgae or plant extracts including macroalgae) is a secure, easy and environmentally friendly method that uses straightforward reducing agents rather than dangerous chemicals [ 14 ]. Numerous uses for nanoparticles (NPs) exist for preserving sustainable agriculture and healthy ecosystems as well as for resolving environmental and agricultural issues.…”
Section: Introductionmentioning
confidence: 99%